Simplify 6(x + 4).

Question

Asked 9/9/2013 8:51:31 AM

Updated 5/25/2014 8:38:17 PM

7 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/25/2014 8:34:41 PM]

Giana|Points 1081|

rhyann24|Points 2455|

thovan213|Points 0|

Question

Asked 9/9/2013 8:51:31 AM

Updated 5/25/2014 8:38:17 PM

7 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/25/2014 8:34:41 PM]

Rating

3

6(x + 4) = 6x + 24

Added 5/25/2014 8:34:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 8:46:59 PM]

3

15x + 2x can be written as (15 + 2)x which is equal to 17x

Added 5/25/2014 8:35:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 8:47:09 PM]

3

All of the following expressions represent the sum of n and itself, except n².

Added 5/25/2014 8:35:53 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 8:47:17 PM]

3

5x + 2x + 7x = 7x + 7x = 14x

Added 5/25/2014 8:36:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 8:47:41 PM]

3

All of the following are equivalent, except (12 + 3x)x.

(12 + 3)x = 12x + 3x = 15x

(12 + 3)x = 12x + 3x = 15x

Added 5/25/2014 8:37:37 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 8:47:41 PM]

3

|x| - |-x| = 0

Added 5/25/2014 8:38:00 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/25/2014 8:55:30 PM]

3

-4x - x = -5x

Added 5/25/2014 8:38:17 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/25/2014 8:55:33 PM]

_____ is an aid to the memory.
Deduce
Mnemonic
Etymology

MNEMONIC is an aid to the memory.

Question

Expert Answered

Updated 3/11/2017 6:55:03 PM

1 Answer/Comment

MNEMONIC is an aid to the memory.

Added 3/11/2017 6:55:03 PM

This answer has been confirmed as correct and helpful.

8(A + 2B) + 6(2A + B).

Question

Expert Answered

Updated 5/31/2014 4:12:11 PM

1 Answer/Comment

8(A + 2B) + 6(2A + B);

8A + 16B + 12A + 6B

= 20A + 22B

8A + 16B + 12A + 6B

= 20A + 22B

Added 5/31/2014 4:12:11 PM

This answer has been confirmed as correct and helpful.

Simplify 18 - 2[x (x - 5)]. User: Simplify 8(C + 10) + 20. **Weegy:** 8(C + 10) + 20 = 8C + 80 + 20 = 8C + 100
**User:** Simplify 6(A + 2) + 5A.
23A
12A + 11
11A + 12 **Weegy:** 6(A + 2) + 5A is equal to 6(A + 2) + 5A , answer is C. SOLUTION: 6(A + 2) + 5A 6A+12+5A 6A+5A+12 11A+12 **User:** Simplify 12 + 3(2x - 3) + 4.
6x - 3
6x + 7
6x + 13 **Weegy:** our answer is: x = 137/41 or 3.34 (More)

Question

Expert Answered

Updated 6/28/2014 11:55:45 AM

6 Answers/Comments

Simplified 18 - 2[x (x - 5)] = -2 (x^2-5 x-9)

Added 6/27/2014 1:18:42 AM

This answer has been flagged as incorrect.

Flagged by yeswey [6/27/2014 3:56:01 PM]

18 - 2[x (x - 5)]

= 18 - 2(x^2 - 5x)

= 18 - 2x^2 + 10x

= -2x^2 + 10x + 18

= 18 - 2(x^2 - 5x)

= 18 - 2x^2 + 10x

= -2x^2 + 10x + 18

Added 6/27/2014 3:55:49 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/30/2014 11:34:18 AM]

12 + 3(2x - 3) + 4

= 12 + 6x - 9 + 4

= 6x + (12 - 9 + 4)

= 6x + 7

= 12 + 6x - 9 + 4

= 6x + (12 - 9 + 4)

= 6x + 7

Added 6/27/2014 3:57:29 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/30/2014 11:36:20 AM]

Jeifunk,

I added the answer for your first question again since the sign was not completely shown. i am afraid later the auto answer should be the same.

I added the answer for your first question again since the sign was not completely shown. i am afraid later the auto answer should be the same.

Added 6/27/2014 3:58:47 PM

27,694,301

questions answered

There are no comments.